Religious Awareness of Mabrur Hajj Pilgrims in Performing the Hajj Pilgrimage based on the Hadith of the Prophet: Kesadaran Beragama Jamaah Haji Mabrur dalam Melakukan Ibadah Haji berdasarkan Hadits Nabi - Muhammad Yusup; Muhammad Mansur; Achmad Dahlan; Mahatva Yoga Adi Pradana (Jurnal Living Hadis, 2024)
As one of the pillars of Islam, the Hajj has great urgency to be carried out by every Muslim who is considered to have the ability. Apart from being an obligation, the Hajj also has many advantages, as explained in the hadith of the Prophet Muhammad. This research examines the congregation's acceptance of the hadith on the virtues of the Hajj and its implementation in carrying out the Hajj pilgrimage through two problem formulations; first, what is the reception of the Hajj pilgrims towards the hadith; and second, what is the form of implementation of the hadith by the congregation? This question was analyzed using a qualitative approach with in-depth interview methods supported by data related to the pilgrims' understanding of the hadith of the virtues of the Hajj and the practices carried out during the Hajj pilgrimage. The research results show that the majority of Hajj pilgrims understand and accept the hadith and the virtues of Hajj well. They try to practice the teachings in the hadith, such as increasing worship, protecting themselves from immoral acts, and increasing spirituality during the Hajj. This shows the high awareness of Hajj pilgrims about carrying out the Hajj pilgrimage as well as possible. This research concludes that the congregation's acceptance of the hadith on the virtues of the Hajj is quite good, and they try to apply it in the implementation of the Hajj, so that this can contribute to a deeper understanding of the dynamics of people's spiritual life.